Anomalous electron doping independent two-dimensional superconductivity. (10th July 2017) - Zhou, Wei; Xing, Xiangzhuo; Zhao, Haijun; Feng, Jiajia; Pan, Yongqiang; Zhou, Nan; Zhang, Yufeng; Qian, Bin; Shi, Zhixiang
Abstract: Transition metal (Co and Ni) co-doping effects are investigated on an underdoped Ca0.94 La0.06 Fe2 As2 compound. It is discovered that electron doping from substituting Fe with transition metal (TM = Co, Ni) can trigger high- T c superconductivity around 35 K, which emerges abruptly before the total suppression of the innate spin-density-wave/anti-ferromagnetism (SDW/AFM) state. Remarkably, the critical temperature for the high- T c superconductivity remains constant against a wide range of TM doping levels. And the net electron doping density dependence of the superconducting T c based on the rigid band model can be nicely scaled into a single curve for Co and Ni substitutions, in stark contrast to the case of Ba(Fe1− x TM x )2 As2 . This carrier density independent superconductivity and the unusual scaling behavior are presumably resulted from the interface superconductivity based on the similarity with the interface superconductivity in a La2− x Sr x CuO4 -La2 CuO4 bilayer. Evidence of the two-dimensional character of the superfluid by angle-resolved magneto-resistance measurements can further strengthen the interface nature of the high- T c superconductivity.